2017
DOI: 10.1002/jwmg.21324
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection and activities of dabbling ducks during non‐breeding periods

Abstract: Western Tennessee is an important region for waterfowl during non‐breeding periods, supporting >40% of the Mississippi Flyway population of American black ducks (Anas rubripes). Understanding habitat selection and activities of waterfowl during the non‐breeding period is important for directed habitat management on national wildlife refuges and in other wetlands important in meeting regional waterfowl conservation objectives. During November–February 2011–2013, we investigated diurnal habitat selection and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 70 publications
(115 reference statements)
2
19
0
Order By: Relevance
“…SAV also provided habitat for aquatic macroinvertebrates, which accounted for 25 kg/ha of food in aquatic bed communities at Emiquon Preserve. In contrast, Hagy and Kaminski () found 0.9–1.8 kg/ha of aquatic macroinvertebrates in actively managed moist‐soil wetlands across the lower Mississippi Alluvial Valley and Osborn et al () found 10.1–20.8 kg/ha during November–February in moist‐soil wetlands in Tennessee. Aquatic bed communities provide the greatest amount of food energy for waterfowl in semipermanent emergent marshes, but the interspersion of cover types is an important predictor of waterbird use across the annual cycle (Kaminski & Prince ; Smith et al ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…SAV also provided habitat for aquatic macroinvertebrates, which accounted for 25 kg/ha of food in aquatic bed communities at Emiquon Preserve. In contrast, Hagy and Kaminski () found 0.9–1.8 kg/ha of aquatic macroinvertebrates in actively managed moist‐soil wetlands across the lower Mississippi Alluvial Valley and Osborn et al () found 10.1–20.8 kg/ha during November–February in moist‐soil wetlands in Tennessee. Aquatic bed communities provide the greatest amount of food energy for waterfowl in semipermanent emergent marshes, but the interspersion of cover types is an important predictor of waterbird use across the annual cycle (Kaminski & Prince ; Smith et al ).…”
Section: Discussionmentioning
confidence: 94%
“…Consequently, we increased production estimates using a standard correction factor (1.72) developed from seed production estimates and SPI values from Stafford et al (). Other cover types, which included mudflat, bare soil, and open water, contained no or very little vegetation and therefore were assumed to contain an insignificant amount of seeds and tubers available to waterfowl (Osborn et al ). Osborn et al () indicated that rapid assessment models used to predict seed production of moist‐soil plants were temporally and spatially robust and accounted for >90% of biomass at sample locations; thus, we assumed our visual assessment models provided reasonable estimates of food density for waterfowl.…”
Section: Methodsmentioning
confidence: 99%
“…Most habitat conservation planning, acquisition, and management to increase local duck populations during the nonbreeding season focus on providing abundant, energy‐rich food (Playa Lakes Joint Venture [PLJV] Waterfowl Team , Soulliere et al ). Food availability can affect local duck abundance and distribution by attracting ducks to food‐rich areas (Brasher , O'Shaughnessy , Hagy et al , Osborn et al ) and influencing stopover duration during migration (O'Neal et al ). Food availability can also affect how ducks use vigilance behavior to govern predation risk (Brown and Kotler , Behney ).…”
mentioning
confidence: 99%
“…Sampling over multiple occasions facilitated estimating food depletion during each period, which may provide an index to intensity of duck use of sites (Hagy and Kaminski ). Based on the attractiveness of moist‐soil wetlands to ducks because of their structure and high food production (Kross et al , Osborn et al ), I predicted that actively managed emergent wetlands (i.e., moist‐soil impoundments) would produce the most energy and exhibit the greatest amount of energy depletion throughout the nonbreeding period. My second objective was to estimate the average percentage of a wetland that was shallow enough to facilitate feeding by dabbling ducks, which represents a major component of how much food is actually available to be consumed.…”
mentioning
confidence: 99%
“…Additionally, the presence of shrubs or dense herbaceous material can provide wildlife shelter. Dabbling duck use of wetlands was positively correlated with dense emergent vegetation (Osborn et al 2017), as it provides thermal cover in the winter (Jorde et al 1984) and possible shielding from predation (Euliss and Harris 1987) in addition to acting as a food resource in the form of seeds and tubers.…”
Section: Discussionmentioning
confidence: 99%